2018
DOI: 10.1093/annonc/mdy075
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects measured by restricted mean survival time in trials of immune checkpoint inhibitors for cancer

Abstract: Ratio of RMST is a complementary technique that provides alternative method of summarizing treatment effects. Proportional hazards of the treatment effect should not be assumed in RCTs evaluating immune checkpoint inhibitors, and RMST analysis should be reported in such trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…It has been shown that HR is a relative measure of the rate of death and tends to overestimate the relative survival benefit. 4,8,21 Comparability of treatment effects of immunotherapy drugs between RMST ratios and HR estimates has also been shown to be in general agreement. 21 It has been suggested that it may be useful to report RMST in immunotherapy trials, in which the benefit typically is at the tail of the curve.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…It has been shown that HR is a relative measure of the rate of death and tends to overestimate the relative survival benefit. 4,8,21 Comparability of treatment effects of immunotherapy drugs between RMST ratios and HR estimates has also been shown to be in general agreement. 21 It has been suggested that it may be useful to report RMST in immunotherapy trials, in which the benefit typically is at the tail of the curve.…”
Section: Introductionmentioning
confidence: 81%
“…4,8,21 Comparability of treatment effects of immunotherapy drugs between RMST ratios and HR estimates has also been shown to be in general agreement. 21 It has been suggested that it may be useful to report RMST in immunotherapy trials, in which the benefit typically is at the tail of the curve. 3,21,22 Because RMST methods seem to be a reasonable alternative approach to measure survival benefits to overcome limitations of conventional measures, our study aimed to quantify the magnitude of survival benefit in oncology drugs recently approved by the FDA, using RMST difference (absolute survival benefit) and RMST ratio (relative survival benefit) in a metaanalysis.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, non-proportional hazards have been frequently reported in ICI trials due to the long-term survival and delayed clinical effect [57,58]. Complementary methods to evaluate treatment effects such as the ratio of restricted mean survival time should be anticipated in pre-planned statistical analyses [59,60].…”
Section: Choosing the Most Accurate Statistical Methodsmentioning
confidence: 99%